2018
DOI: 10.1111/acer.13860
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Motivation to Self‐Administer Alcohol After 2 Weeks of Abstinence in Young‐Adult Heavy Drinkers

Abstract: We believe a more comprehensive study of mechanisms underlying the sex differences in the human postabstinence response is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 84 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…Sex differences in alcohol intake and preference are well recognized in animals and humans, with females generally drink more alcohol than males [30][31][32][53][54][55]. Consistent with this, average daily alcohol intake in female Bmal1CTR mice was significantly greater than in Bmal1CTR males (P<0.0001, unpaired two-tailed t test) and mean alcohol preference was significantly higher in Bmal1CTR females than Bmal1CTR males (P<0.05, unpaired two-tailed t test) ( Supplementary Fig.…”
Section: Deletion Of Bmal1 or Per2 From Msns Eliminates Sex Differencsupporting
confidence: 67%
“…Sex differences in alcohol intake and preference are well recognized in animals and humans, with females generally drink more alcohol than males [30][31][32][53][54][55]. Consistent with this, average daily alcohol intake in female Bmal1CTR mice was significantly greater than in Bmal1CTR males (P<0.0001, unpaired two-tailed t test) and mean alcohol preference was significantly higher in Bmal1CTR females than Bmal1CTR males (P<0.05, unpaired two-tailed t test) ( Supplementary Fig.…”
Section: Deletion Of Bmal1 or Per2 From Msns Eliminates Sex Differencsupporting
confidence: 67%
“…In humans, a progressive ratio trial of intravenous alcohol self-administration showed that women increased their work effort to obtain alcohol after resumption following 2 weeks of abstinence, whereas men decreased this effort. 113 Male rats exposed to alcohol vapors to produce dependence display increased compulsive-like behavior and increased intake on both fixed and progressive ratio schedules. 88 However, progressive ratio tests in Long Evans rats suggest there is no sex difference in motivation for alcohol, at least following extinction and reinstatement of alcohol self-administration.…”
Section: Preoccupation/anticipation Stagementioning
confidence: 99%
“…Free access to alcohol rewards is available for a prescribed period of time (usually 2 to 3 hours), with maximum BrAC levels allowed up to a predetermined safety limit. Because there is good accuracy of achieving the target BrAC, maximum allowable BrAC levels range up to 200 mg/dl, although most infusion self‐administration studies set the limit between 100 and 180 mg/dl (e.g., Plawecki et al, 2018b; Stangl et al, 2017; VanderVeen et al, 2016).…”
Section: Comparing and Contrasting Paradigmsmentioning
confidence: 99%
“…The literature associating intravenous alcohol self‐administration paradigms with behavioral and clinical phenotypes is emerging. Intravenous alcohol self‐administration has been associated with family history of alcoholism (Zimmermann et al, 2009), drinking history (Bujarski et al, 2018; Stangl et al, 2017), including binge drinking (Sloan et al, 2019), AUD risk (Gowin et al, 2017), craving (Green et al, 2019; Wardell et al, 2015), personality traits (Stangl et al, 2017; VanderVeen et al, 2016), sex differences (Cyders et al, 2016; Plawecki et al, 2018b), pharmacologic targets or interventions (Suchankova et al, 2017), and risk genotypes (Hendershot et al, 2016, 2017; Plawecki et al, 2013; Sloan et al, 2018; Suchankova et al, 2017).…”
Section: Issues To Consider In Choosing Route Of Administrationmentioning
confidence: 99%